An Analysis of Digital Social Validation Behavior in Adolescents: Implications for Creative Counseling - Ristra Sandra Ritonga; Annisa May Syarah Nasution; Utami Nurhafsari Putri; Rizki Ananda Syafitri; Rezi Akbar Zarnazi (Universitas Negeri Medan, 2026)
The rapid growth of social media has transformed the way adolescents build social relationships and seek recognition through various forms of digital social validation, such as likes, comments, and followers. This phenomenon has the potential to influence adolescents' social and psychological behavior, thereby requiring greater attention within Guidance and Counseling services. This study aimed to explore adolescents' digital social validation behavior and identify its implications for the development of creative counseling. A descriptive-exploratory research design was employed involving 125 adolescents aged 18–23 years who actively use social media. The research instrument consisted of a Digital Social Validation Behavior Questionnaire developed using a five-point Likert scale and open-ended questions. The data were analyzed using descriptive statistical analysis, while responses to the open-ended questions were examined through thematic analysis. The findings revealed that the attention to digital feedback indicator demonstrated the highest tendency (mean = 3.56–4.42), whereas the remaining indicators were categorized as moderate to high. The thematic analysis further indicated that adolescents primarily use social media for communication, entertainment, and self-expression. In addition, respondents preferred experience-based counseling activities, particularly nature-based activities (56.5%), storytelling (43.5%), and music-based activities (42.4%). The study concludes that Guidance and Counseling services should adopt more contextual, participatory, and developmentally appropriate creative counseling approaches that align with the characteristics of adolescents in the digital era. The findings are expected to serve as an empirical foundation for guidance and counseling teachers and professional counselors in designing creative counseling services that are more responsive to the dynamics of adolescents' digital behavior.